Bioactivity of Size-Fractionated and Unfractionated Humic Substances From Two Forest Soils and Comparative Effects on N and S Metabolism, Nutrition, and Root Anatomy of Allium sativum L - Pizzeghello, Diego; Schiavon, Michela; Francioso, Ornella; Dalla Vecchia, Francesca; Ertani, Andrea; Nardi, Serenella (Frontiers in Plant Science, 2020)
Humic substances (HS) are powerful natural plant biostimulants. However, there is still a lack of knowledge about the relationship between their structure and bioactivity in plants. We extracted HS (THE1-2) from two forest soils covered with Pinus mugo (1) or Pinus sylvestris (2). The extracts were subjected to weak acid treatment to produce size-fractionated HS (high molecular size, HMS1-2; low molecular size, LMS1-2). HS were characterized for total acidity, functional groups, element and auxin (IAA) contents, and hormone-like activity. HS concentrations ranging from 0 to 5 mg C L-1 were applied to garlic (Allium sativum L.) plantlets in hydroponics to ascertain differences between unfractionated and size-fractionated HS in the capacity to promote mineral nutrition, root growth and cell differentiation, activity of enzymes related to plant development (invertase, peroxidase, and esterase), and N (nitrate reductase, glutamine synthetase) and S (O-acetylserine sulphydrylase) assimilation into amino acids. A positive linear dose-response relationship was determined for all HS in the range 0-1 mg C L-1, while higher HS doses were less effective or ineffective in promoting physiological-biochemical attributes of garlic. Bioactivity was higher for size-fractionated HS according to the trend LMS1-2>HMS1-2>THE1-2, with LMS2 and HMS2 being overall more bioactive than LMS1 and HMS1, respectively. LMS1-2 contained more N, oxygenated functional groups and IAA compared to THE1-2 and HMS1-2. Also, they exhibited higher hormone-like activities. Such chemical properties likely accounted for the greater biostimulant action of LMS1-2. Beside plant growth, nutrition and N metabolism, HS stimulated S assimilation by promoting the enrichment of garlic plantlets with the S amino acid alliin, which has recognized beneficial properties in human health. Concluding, this study endorses that i) treating THE with a weak acid produced sized-fractionated HS with higher bioactivity and differing in properties, perhaps because of novel molecular arrangements of HS components that better interacted with garlic roots; ii) LMS from forest soils covered with P. mugo or P. sylvestris were the most bioactive; iii) the cover vegetation affected HS bioactivity iv); HS stimulated N and S metabolism with relevant benefits to crop nutritional quality.